2007
DOI: 10.3174/ajnr.a0741
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CT Angiography with Matched Mask Bone Elimination for Detection of Intracranial Aneurysms: Comparison with Digital Subtraction Angiography and 3D Rotational Angiography

Abstract: BACKGROUND AND PURPOSE: Our aim was to determine the diagnostic accuracy of multisection CT angiography combined with matched mask bone elimination (CTA-MMBE) for detection of intracranial aneurysms compared with digital subtraction angiography (DSA) and 3D rotational angiography (3DRA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 34 publications
1
49
0
3
Order By: Relevance
“…31,32 Interobserver agreement in our study was somewhat higher than that reported previously. 11,17,19,26 Intraobserver agreement was excellent as in another study by Lu et al 11 We had excellent interreader agreement for aneurysm identification and configuration. Our results are in line with those in other studies, 17,26 even with a recent study with 320 -detector row BSCTA 33 comparing CTA with intraoperative observations.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…31,32 Interobserver agreement in our study was somewhat higher than that reported previously. 11,17,19,26 Intraobserver agreement was excellent as in another study by Lu et al 11 We had excellent interreader agreement for aneurysm identification and configuration. Our results are in line with those in other studies, 17,26 even with a recent study with 320 -detector row BSCTA 33 comparing CTA with intraoperative observations.…”
Section: Discussionsupporting
confidence: 50%
“…CTA has a high sensitivity and specificity in detecting intracranial aneurysms, 8,9,11,12,17,19,20 but skull base structures can hide adjacent aneurysms. 17,21 Bone-subtraction CTA 22,23 has been developed to overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In an article published in 2007 by Ishihara et al, this was studied and confirmed in a small collective of 15 patients [10]. Other studies evaluate different advantages of 3 D DSA, e. g. the number of detected aneurysms [11], and the advantages of 3 D DSA for treatment planning [12] and for treatment success monitoring [13]. We also use 3 D DSA for diagnostic verification of bleeding source as well as for intervention/ operation planning.…”
mentioning
confidence: 72%
“…Manual bone editing in CTA is a time-consuming and user-dependent process that relies on a knowledge of vascular anatomy (13,14). Matched mask bone elimination (MMBE) is a relatively new technique that enables bone removal in an automatic and user-independent way (18,22). In CTA-MMBE, a second, non-enhanced scan is necessary for the identification of bony structures that could be masked in the CTA scan.…”
Section: Per-patientmentioning
confidence: 99%